Silkworm (Tubifer sp) Business Development Through a Combination Model of Flowing Water Circulation and Vegetables - Rayandra, Asyar; Musnandar, Endri; Tani, Sri Arnita Abu (Talenta Publisher Universitas Sumatera Utara, 2022)
Single Parent women in Pudak Village high, namely around 200 people.Being a Single Parent Woman is of course required to be independent so that they can make their children successful and have a better life. One solution that can be done is to empower single parent women to become strong women so they can prosper in their families, through cultivation activities for the development of silkworm (Tubifer sp) cultivation as freshwater fish seed feed, because currently there are quite large marketing opportunities, and there are still unable to meet market demand. To achieve the objective of the activity, technology transfer was carried out, through the implementation of the silkworm cultivation model using a running water system with vegetable feed ingredients such as carrots, mustard greens, tomatoes, and carrots which are market waste that is no longer utilized. The form of technology transfer that is applied through the Learning by doing model. The results obtained show that single-parent women can cultivate silkwormsand understand the use of market waste in the form of waste vegetables (mustard), and fruits (tomatoes, papayas, oranges, banana peels).